1987
DOI: 10.1080/0260741870130302
|View full text |Cite
|
Sign up to set email alerts
|

The Construction of Subjectivity in Educational Television. Part Two:You and Me‐‐a case study

Abstract: This case study represents an application of the theoretical approach outlined in the first part of this article, published in the Journal of Educational Television, 13 (2). It is based on an analysis of programmes in the BBC series for preschool children You and Me, transmitted in the school year 1984-85. It provides an illustrated typology of the modes of subject positioning employed in the series, and a comparative analysis identifying changes in its pedagogic style over the past five years. It concludes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Analysis of the interviews showed that responses to the programmes varied in ways which were not directly related to social class variables but to gender and ethnic differences (Morley, 1980). Similar responses were shown by viewers in studies carried out by Buckingham (Buckingham, 1987). In an earlier study, he found that some viewers of the programme 'The Whites of their Eyes' in Thames' Viewpoint 2 series had difficulty in distinguishing the voice-over commentary from individual views expressed in the programme, and that their failure to understand its basic mechanics meant that they failed to grasp many of the points it was trying to make.…”
Section: Understanding Television Audiences 17mentioning
confidence: 53%
“…Analysis of the interviews showed that responses to the programmes varied in ways which were not directly related to social class variables but to gender and ethnic differences (Morley, 1980). Similar responses were shown by viewers in studies carried out by Buckingham (Buckingham, 1987). In an earlier study, he found that some viewers of the programme 'The Whites of their Eyes' in Thames' Viewpoint 2 series had difficulty in distinguishing the voice-over commentary from individual views expressed in the programme, and that their failure to understand its basic mechanics meant that they failed to grasp many of the points it was trying to make.…”
Section: Understanding Television Audiences 17mentioning
confidence: 53%
“…There have been a number of approaches to the problems of increasing the skills of the viewer, and these are by no means similar in their theoretical approach or their practical implications (Buckingham, 1987(Buckingham, , 1990Buckle & Kelley, 1990;Dorr et al, 1983;Lloyd-Kolkin et al, 1980;Roberts et al, 1980;Rapaczynski, 1982;Singer et al, 1988). It is interesting that many of these approaches were predicated on the supposed negative effects of the medium (the contrast here with attitudes to reading are quite striking).…”
Section: Introductionmentioning
confidence: 91%
“…He made the important point that each of the approaches tended to evaluate the success of programmes of learning by different criteria. More recently Buckingham (1987) and others have suggested the 'negotiated meaning' approach. This model suggests that the individual members of the audience have a important part in creating the meaning of any television broadcast.…”
Section: Introductionmentioning
confidence: 98%